Gut microbiota variation of a tropical oil-collecting bee species far exceeds that of the honeybee - Kardas, Elif; González-Rosario, Angie M.; Giray, Tugrul; Ackerman, James D.; Godoy-Vitorino, Filipa (Frontiers in Microbiology, 2023)
Interest for bee microbiota has recently been rising, however, no study has addressed the microbial acquisition routes of tropical solitary bees. While social bees such as honeybees maintain a constant gut microbiota by direct transmission from individuals of the same hive, solitary bees do not have direct contact between generations. They thus acquire their gut microbiota from the environment and/or the provision of their brood cell. To establish the role of life history in structuring the gut microbiota of solitary bees, we characterized the gut microbiota of Centris decolorata from a beach population in Mayagüez, Puerto Rico. Females provide the initial brood cell provision for the larvae, while males patrol the nest without any contact. We hypothesized that this behavior influences their gut microbiota, and that the origin of larval microbiota is from brood cell provisions. We collected samples from adult females and males of C. decolorata (n=10 each, n=20), larvae (n=4), and brood cell provisions (n=10). We also sampled co-occurring female foragers of social Apis mellifera (n=6). Pollen loads of A. mellifera and C. decolorata were analyzed and interactions between bees and plant resources were visualized in a network. While we found the gut of A. mellifera contained the same phylotypes previously reported in the literature, we noted that the variability in the gut microbiota of solitary C. decolorata was significantly higher than that of social A. mellifera. Furthermore, the microbiota of adult C. decolorata mostly consisted of acetic acid bacteria whereas that of A. mellifera mostly had lactic acid bacteria. Among C. decolorata, we found significant differences in alpha and beta diversity between adults and their brood cell provisions associated with higher abundance of Rhizobiaceae and Chitinophagaceae in the brood cells, and of Acetobacteraceae in adults. Pollination network analysis indicated that a stronger interaction of A. mellifera with Byrsonima sp. and a weaker interaction with Combretaceae. Interactions between C. decolorata and plant resources were constant with the null model. Our data is consistent with the hypothesis that brood provisioning in solitary bees leads to high variation in their gut microbiota